Prospective memory 7 years after severe childhood traumatic brain injury – the TGE 2 prospective longitudinal study. (3rd October 2017) - Krasny-Pacini, Agata; Francillette, Leila; Toure, Hanna; Brugel, Dominique; Laurent-Vannier, Anne; Meyer, Philippe; Evans, Jonathan; Chevignard, Mathilde
ABSTRACT: Objective : To investigate the long-term outcome in prospective memory (PM), seven years after childhood severe traumatic brain injury (TBI), in a prospective longitudinal cohort. Participants : 76 young individuals (aged 7–22 years): 39 patients with a severe accidental TBI included prospectively seven years earlier, aged 0–15 years at injury, and 37 controls individually matched on age, gender and parental education. Main outcome measures : Three novel short PM tasks varying in the delay, motivation and context (ecological versus paper and pencil task). Results : Individuals with severe TBI showed significantly poorer PM than matched controls in the two low-motivation PM tasks: (1) the ecological long-delay task consisting of sending a letter on a rainy day ( p =0.047, odds ratio = 2.6); (2) the non-ecological short-delay task consisting of taking off post-its while identifying facial emotions ( p =0.004, r =0.34). Differences in PM on the high motivation were not significant. PM is impaired several years post severe TBI.